The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5424/sjar/20110902-161-10
|View full text |Cite
|
Sign up to set email alerts
|

Simple sequence repeat (SSR) vs. sequence-related amplified polymorphism (SRAP) markers for Cynara cardunculus characterization

Abstract: A little is known about the genetic variability present in globe artichoke, cultivated and wild cardoons. This knowledge is very important for efficient genetic resources utilization, and to gain a better understanding of genetic structure of this botanical varieties. With the aims to determine genetic distances between Cynara cardunculus accessions and to compare two molecular markers systems for their efficiency to differ between botanical varieties, a molecular characterization of sixteen accessions from di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Wild cardoon SSR polymorphism showed that all populations were clearly distinguished from each other suggesting high performance of the SSR as molecular tools for genetic identification. Similar studies using microsatellites to analyze populations of Cynara showed high levels of polymorphism (Casadevall et al, 2011;Gatto et al, 2013). Overall, the results of molecular markers analysis revealed a high gene diversity of wild cardoon populations (He = 0.77) and supported those found by Khaldi et al (2012) for Tunisian wild cardoon genotypes.…”
Section: Discussionsupporting
confidence: 75%
“…Wild cardoon SSR polymorphism showed that all populations were clearly distinguished from each other suggesting high performance of the SSR as molecular tools for genetic identification. Similar studies using microsatellites to analyze populations of Cynara showed high levels of polymorphism (Casadevall et al, 2011;Gatto et al, 2013). Overall, the results of molecular markers analysis revealed a high gene diversity of wild cardoon populations (He = 0.77) and supported those found by Khaldi et al (2012) for Tunisian wild cardoon genotypes.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, the electrophoresis in agarose gel used in SRAP markers is faster and less laborious than the electrophoresis in polyacrylamide gel for microsatellites. On the other hand, Casadevall et al (2011), using microsatellites and SRAP markers to study the genetic diversity of Cynara cardunculus, recommended to use microsatellite markers for their easy visualization and codominance information. The fact that in this study as well as in our research (Table 6) the estimators of genetic diversity obtained by SRAP appear lower than those obtained by microsatellite might be due to the characteristics of the marker system.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies (Cravero, Martin and Cointry, 2007;Casadevall, Martin and Cravero, 2011), the variability available between some accessions, belonging to the local C. cardunculus collection, was evaluated using Sequence Related Amplified Polymorphism (SRAP) (Li and Quiros, 2001). Those studies proved that SRAP is also a helpful tool to detect genetic diversity in this species and to classify accessions into groups based on their genetic distance values.…”
Section: Introductionmentioning
confidence: 99%